PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN STUDI KASUS DI SMK KARTIKA V-I BALIKPAPAN - meilita rizki (Lembaga Penelitian Universitas Balikpapan, 2020)
Abstract— Library system of Kartika V-I Balikpapan Vocational High School still using a manual process for loan books and reporting, such as reporting book loans. The development of the library system will objectify Slims for the control automation process for book loans and reporting so that the production process works effective and efficient. This system consists of book loans and daily loan reporting. The book loan process consists of a daily loan and book returns. This system will use library database management. Technological This process begins after the installation process been done. Starting from loan books, return book and reporting using Senayan Library management system (SLIMS). The previous library system will not be used anymore after development. The test result can be concluded that the process for loan and return book by the library information system more effective and efficient than manual process. The connection between xampp database and library information system works well.